On Being Here to Stay: Treaties and Aboriginal Rights in Canada - MICHAEL ASCH (University of Toronto Press, 2014)
I started out to write a book that would need little further research. It was to be a book that put in one place a position on the political relationship between Indigenous peoples and the Canadian state that I had been developing for thirty years and more. But that is not the book I have written. The first four chapters did go as planned. They are largely a rendering of key features of my argument on the theme just mentioned. But beginning with the fifth chapter, I embarked on an adventure that led me to include information of which I was already knowledgeable but never thought would be relevant, as well as information that was entirely new, at least to me. That is the manuscript I presented to the University of Toronto Press. Here is what happened. The position I have long held rests on the principle, as confirmed in the 1960 United Nations Declaration on the Granting of Independence to Colonial Countries and Peoples (or simply the Declaration on De- Colonization), to which Canada is a signatory, that, at least with respect to colonized peoples, it is wrong legally as well as morally to move onto lands belonging to others without first obtaining their permission. The centrepiece of my approach to reconciling this principle with the fact that Canada is on lands that belong to Indigenous peoples was to determine what permission from them might entail; and to that end I chose to look in particular at what Indigenous peoples today explain are the terms of treaties made with the Crown in the past that permitted settlement on their lands. I had no intention to delve into whether there had been agreement on these terms in the past. Rather, I reasoned that, whether or not such agreement had existed when the treaties were negotiated, the terms of these treaties, as Indigenous peoples present them today, serve as a proxy (by which I also mean an approximation) for what would be their position on the terms of an arrangement with the state were Canada now seeking to act in compliance with the UN Declaration.